Morphological and molecular characterization of multiple new Azadinium strains revealed a high diversity of non‐toxigenic species of Amphidomataceae (Dinophyceae) including two new Azadinium species in Irish waters, North East Atlantic. Issue 2 (4th January 2021) - Salas, Rafael; Tillmann, Urban; Gu, Haifeng; Wietkamp, Stephan; Krock, Bernd; Clarke, Dave
SUMMARY: Shellfish contamination with azaspiracids (AZA), which are lipophilic marine biotoxins produced by marine dinoflagellates, is a major and recurrent problem for the Irish shellfish industry. AZA are produced by certain species of Amphidomataceae, but the species diversity of this group of microalgae in Irish waters is poorly known. Here we present a morphological and molecular characterization of multiple new strains of non‐toxigenic Azadinium isolated on an oceanographic survey in 2018. A lack of AZA production for all strains presented here was demonstrated by LC‐MS/MS analysis. One strain of Azadinium caudatum var. margalefii (first strain for the area) confirmed non‐toxigenicity of Atlantic populations of this species. One strain designated as Azadinium cf. zhuanum was similar to Az. zhuanum described from China but differed from the type strain in nucleus position, by the dominant number of apical plates, and by significant differences in rRNA gene sequences. Finally, two new non‐toxigenic Azadinium species are described from the North East Atlantic: Azadinium galwayense sp. nov. and Azadinium perfusorium sp. nov. Azadinium galwayense differed from other Azadinium by a characteristic combination regarding presence and location of the ventral pore (vp; on the right side of the pore plate), of a pyrenoid (located in the episome), and by a pentagonal shape of the median anterior intercalary plate 2a, and lack of contact between plates 1″ and 1a. Azadinium perfusorium shared the same vp position as Az. galwayense and differed by a characteristic combination of a pyrenoid located in the hyposome, a tetragonal shape of plate 2a, and a relatively large size of the two lateral anterior intercalary plates. Molecular phylogeny confirmed the distinctiveness of these two new species and their placement in Azadinium . The present findings significantly increased knowledge on the diversity of Azadinium species in the North East Atlantic.